Logicality as Necessary Instantiation - Roderick Batchelor (Revista de Filosofia Moderna e Contemporânea, 2018)
We propose to define logicality of a simple notion as necessary instantiation. (And then logicality of a complex notion as logicality of all simple notions occurring in it.)